Relationships between Obstructive Sleep Apnea Syndrome, Continuous Positive Airway Pressure Treatment, and Inflammatory Cytokines - Ünüvar Doğan, Filiz (Hindawi Publishing Corporation, 2014)
The cardiovascular complications that frequently accompany obstructive sleep apnea syndrome (OSAS) are thought to develop as a result of inflammatory stress associated with cytokines such as IL-6 and TNF-α. We conducted the current study to compare levels of these cytokines in OSAS patients (n = 33) and nonapneic controls (n = 24). Furthermore, we investigated the impact of a three-month regime of continuous positive airway pressure (CPAP) on serum levels of IL-6 and TNF-α only in the OSAS patients. There were no significant differences in serum levels of either IL-6 (P = 0.782) or TNF- α (P = 0.722) or TNF-α (P = 0.722) between OSAS patients and nonapneic controls. Serum IL-6 levels correlated significantly with neck circumference in OSAS patients (P = 0.006). In OSAS patients, reduced levels of TNF-α and IL-6 correlated with increases in mean SaO(2) after CPAP treatment (P = 0.020 and P = 0.051, resp.). However, neither of cytokine levels was significantly impacted by CPAP therapy (both P > 0.137). We have demonstrated that plasma cytokine levels are similar in both otherwise healthy subjects with OSAS and in nonapneic control, and we conclude that OSAS-related parameters and CPAP treatment do not play a significant role in altering cytokine levels.